Successful silencing of plasminogen activator inhibitor-1 in human vascular endothelial cells using small interfering RNA - Hecke, Anneke; Brooks, Hilary; Meryet-Figuière, Matthieu; Minne, Stephanie; Konstantinides, Stavros; Hasenfuss, Gerd; Lebleu, Bernard; Schäfer, Katrin (Thrombosis and Haemostasis, 2006)
Clinical as well as experimental evidence suggests that vascular overexpression of plasminogen activator inhibitor (PAI)-1, the primary physiological inhibitor of both urokinase and tissuetype plasminogen activator, may be involved in the pathophysiology of atherosclerosis and cardiovascular disease. We investigated the feasibility, efficacy and functional effects of PAI-1 gene silencing in human vascular endothelial cells using small interfering RNA. Double-stranded 21 bp-RNA molecules targeted at sequences within the human PAI-1 gene were constructed. Successful siRNA transfection of HUVEC was confirmed using fluorescence microscopy and flow cytometry. One of five candidate siRNA sequences reduced PAI-1 mRNA and protein in a concentrationand time-dependent manner. Suppression of PAI-1 mRNA was detected up to 72 hours after transfection. Moreover, siRNA treatment reduced the activity of PAI-1 released from HUVEC, and prevented the oxLDL- or LPS-induced upregulation of PAI-1 secretion. Importantly, siRNA treatment did not affect the expression of other endothelial-cell markers. Moreover, downregulation of PAI-1 significantly enhanced the ability of endothelial cells to adhere to vitronectin, and this effect could be reversed upon addition of recombinant PAI-1. SiRNAmediated reduction of PAI-1 expression may be a promising strategy for dissecting the effects of PAI-1 on vascular homeostasis.
Keywords: Cell adhesion; fibrinolysis; endothelial cells; plasminogen activator inhibitor-1; RNA interference